Forming a Superior Personality in the Qur'an Epistemological Study of Sahl Al-Tustari's Sufistic Tafsir on Q.S Al-Ikhlas - Lailatul Jannah Firdausi Nuzula; Luthviyah Romziana; Abdur Rahman Nor Afif Hamid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Surah Al-Ikhlas, as one of the chapters in the Quran, consists of four concise yet profoundly meaningful verses. This particular surah delves into the attributes of Allah and holds a central focus in the epistemology of Sufi interpretation, especially in the practice of tariqah by Sufi practitioners. This research aims to unveil the messages contained within Surah Al-Ikhlas through the epistemological study of Sufi interpretation by Sahl al-Tustari. The surah is not merely regarded as a sacred text but also as a guide to understanding spirituality and shaping an excellent personal character, particularly in the context of Sufism. While various approaches to Surah Al-Ikhlas have been explored in previous research, there is a gap in exploring the epistemology of Sufi interpretation by Sahl al-Tustari. By comprehending his views and interpretations of Surah Al-Ikhlas, it is anticipated that a profound understanding of the spiritual dimension and personal experience in comprehending the essence of the Quranic text can be achieved. The research methodology involves analyzing the works of Sahl al-Tustari, focusing on the maudhu’i method and Sufi approach. The findings of this research are expected to contribute to a general understanding of the epistemology of Sufi interpretation, particularly in the context of Surah Al-Ikhlas, and uncover the spiritual values within the Quranic text.